Inoculum development in 2L stirred tank fermenter for production of PHB biopolymer in a 20 L stirred tank fermentation on a medium of oil palm frond juice (OPFJ) - Nahdiyyah, Rosslan (2013)
Polyhydroxybutyrate (PHB) is a biopolymer plastic as intracellular product of bacteria which can be degradable naturally. The purpose of this experiment is to scale up the production of PHB biopolymer by Cupriavidus Necator using oil palm frond juice (OPFJ) as carbon source. The process will involve fermentation process, the analysis on cell dry weight and concentration of PHB. The fermentation will be done in the 2 L stirred tank fermenter model Sartorius with the combination of 450 ml oil palm frond juice, 150 ml inoculum development 2, and 900 ml mineral salt medium (MSM) by manipulating the agitation speed and fixed the aeration rate at 1.5 L/min. Next, the cell dry weight and PHB will be analyse. From the result of DOT curve, 200 rpm in fermenter shows the same pattern as in 220 rpm in flask. 200 rpm is used in 2L fermentation. Highest PHB yield for fermentation in 2 L was 2.0650 g/L and highest cell dry weight was 5.7 g/L. While for cascade fermentation highest cell dry weight was 9.5 g/L and highest PHB content was 5.42 g/L.